Influence of outdoor advertisements on architecture in the City of Lublin - Kozak, Małgorzata (Budownictwo i Architektura / Civil and Architectural Engineering, 2022)
Polish cities are currently facing an issue of intrusive billboards obstructing the faacades of buildings. While the majority of articles on this subject focus on the negative impact this phenomenon, little attention is drawn to the destructive technical effects the advertisements have on the facades. This article addresses phenomenon of visual pollution examins the influence of based on the example of selected buildings located in Lublin’s City Centre. The article analyses the placement of advertising signs, and categorizes of most technical and social problems that it entails. The relation between the occurrence of outdoor advertising and the increase in anti-social behaviour in commercialised space, raised in the article, could be a very important topic for further research. The results of the conducted study reveal that the installation of advertising billboards irreversibly damages the facades of buildings, which is especially visible when the advertisements are removed. The article complements the study on outdoor advertising, drawing attention to one of its little-discussed, technical aspects. Consequently, it may serve as a starting point for further discussion on the subject.